Kajian Daya Dukung Tata Air sebagai Upaya Perencanaan Pengelolaan Daerah Aliran Sungai (DAS) yang Berkelanjutan (Studi Kasus pada DAS Dodokan, NTB, Indonesia) - Muhammad Khalis, Ilmi; Swahip, Swahip; Hidayat, Ari Ramadhan; Fibriyanti, Baiq Vina (Universitas Muhammadiyah Surabaya, 2025)
Monitoring and Evaluation (M&E) of Watershed (DAS) Performance is crucial to assess the Carrying Capacity of the Watershed and can subsequently serve as feedback for improving future watershed management planning. The study on the carrying capacity of water management in the Dodokan Watershed (DAS) is conducted as part of the M&E of watershed performance, considering that the Dodokan Watershed is one of the four main watersheds on Lombok Island, which plays a strategic role due to its high utility in water supply. This study aims to assess the performance of the Dodokan Watershed by measuring its carrying capacity using several parameters, including Flow Regime Coefficient (KRA), Flood Occurrence Frequency (FKB), Water Use Index (IPA), Annual Flow Coefficient (KAT), Sediment Load (MS), and Environmental Flow (EF). Each parameter will be assigned a score and categorized based on the Minister of Forestry Regulation No. P.61/Menhut-II/2014 regarding Monitoring and Evaluation of Watershed Management. The results of the study show that the carrying capacity of the Dodokan Watershed tends to fluctuate but is generally in the moderate category. Overall, the carrying capacity value of the Dodokan Watershed is 95, with an average value of 105, which places the watershed in the moderate carrying capacity category (90 < DDD < 110). Therefore, sustainable watershed management is necessary, with a focus on reducing KRA, MS, and FKB values, as well as increasing KAT, IPA, and EF values. Recommended efforts include the implementation of soil and water conservation techniques for the maintenance of catchment areas, as well as vegetation management for biodiversity conservation and land rehabilitation.